The road less traveled: how to grow a pancreas transplant program. Issue 4 (August 2018) - Abrams, Peter; Cooper, Matthew; Odorico, Jon S.
Abstract : Purpose of review: The volume of pancreas transplants performed annually in the United States (US) has steadily declined for more than a decade. In the face of this negative trend, efforts at several centers are underway to expand their pancreas transplant volumes through alterations in the structure and function of their pancreas transplant programs. We highlight these programmatic changes and emphasize the culture and characteristics of these high volume centers to serve as models for other centers to emulate. As the results of modern-day pancreas transplantation are excellent and continue to improve, pancreas transplant remains an outstanding option for selected patients suffering from diabetes mellitus and end stage renal disease (ESRD) or symptomatic hypoglycemic events (SHEs). Through strong leadership commitment and programmatic restructuring, the transformation of low-volume pancreas transplant centers into high-volume programs is achievable without the need for cost-prohibitive investment. Recent findings: Multiple examples may be cited of transplant centers reinvigorating their pancreas transplant programs, increasing their pancreas transplant evaluations and transplant rates, through personnel reorganization and operational restructuring. As a means of providing a roadmap to encourage other transplant centers to re-energize their pancreas transplant programs, we will outline strategies that can be readily instituted to transform a pancreas transplant program, and delineate the basic steps that any transplant center can take to achieve high-volume success. Summary: The negative trends in access to pancreas transplantation in the US may ultimately be addressed by low-volume pancreas transplant programs re-committing themselves through easily achievable institutional changes without substantial added capital investment, thereby maximizing access to pancreas transplantation for their diabetic patients and maintaining excellent outcomes.